Catching children as they fall: mental health promotion in residential child care in East Dunbartonshire - Michael van Beinum; Andy Martin; Chris Bonnett (Scottish Journal of Residential Child Care)
This article will outline the first years of a joint project to develop a dedicated mental health service for looked after and accommodated children, which was developed between residential child care managers in East Dunbartonshire and the North Glasgow Community Adolescent Mental Health (CAMH) team. It will start by describing the events that led up to the setting of the project, and go on to outline the project itself. It will conclude with a discussion of some of the philosophical underpinnings of the project and suggestions for future developments.